Analisis Biaya Terapi Pada Penderita Stroke Pasien Rawat Inap Di RSUD Dr. Moewardi Surakarta Bulan Januari - Juni 2015 - Prabowo, Ahmad; , Dr. dr. EM. Sutrisna, M.Kes; , Gunawan Setiyadi, M.Sc., Apt (2016)
ABSTRACT Stroke was the highest group of diseases in the community. Treatment of stroke requires considerable costs due to the physical effects caused by stroke. Their health insurance from the government (BPJS) on the one hand ease the burden on society, but on the other hand the use of generic drugs that have a quality below the common drugs have an impact on patient care processes that tended to last longer. The purpose of this study was to determine the cost of treatment of stroke in patients hospitalized in the Hospital "X" Surakarta January to June 2015 in terms of the type of financing and diagnosis of stroke. This study was a non-experimental study, with descriptive method. The study population was patients with stroke in hospital "X" Surakarta January-June 2015, while the study sample of 145 stroke patients with purposive sampling technique. Collecting data using documentation were analyzed using descriptive techniques. To review component covers the cost of Direct include: (1) covers the cost of the drug, (2) covers hospitalization costs, (3) covers the cost of Physicians, (4) covers laboratory expenses, (5) covers the cost of scanning, (6) covers administrative costs. Based on the results of research and discussion the conclusions of the study are (1) the total cost of non-hemorrhagic stroke patients with non BPJS financing obtained an average total cost of 5,395,915 whereas hemorrhagic stroke in patients with an average total cost of6,686,669, (2) the total cost of hemorrhagic stroke patients with BPJS financing on non hemorrhagic stroke patients the average total cost of. 2,317,194 while in hemorrhagic stroke 3269191, (3) the average total cost of treatment in patients with non BPJS (5,666,557) than patients BPJS (2,741,076) and average total cost of patient non-hemorrhagic stroke (3,911,488) lower than the average total cost of hemorrhagic stroke patients (4,140,313), and (4) the cost component of the most widely issued by the patients was the cost of hospitalization.